Shipping - Christensen, Tom; Lasserre, Frédéric; Dawson, Jackir; Guy, Emmanuel; Pelletier, Jean-François (Arctic Monitoring and Assessment Programme (AMAP), 2018)
The Baffin Bay/Davis Strait (BBDS) region depends heavily on shipping. This sector is an important driver of economic activity. • Shipping in the region is generally expected to benefit from climate change. This benefit will probably facilitate some growth in the industry. • However, other drivers of change are probably more important than climate change. Other important drivers include issues of geopolitics (e.g., Suez and Panama canals, political issues outside the region), global and regional economies (e.g., effects on mining, oil exploration/ exploitation, and other industries), national priorities (e.g., deep-water port projects along the Canadian coast), and insurance (i.e., winter shipping versus summer shipping). • Increased shipping may bring some positive economic impacts to the region. However, local residents express concern for the social, cultural, and environmental effects related to expansion. • Shipping-related environmental impacts on ecosystems and species in the region include oil (and chemical) spills; noise and disturbance, underwater and above; garbage (including organic); invasive species; and light (i.e., artificial illumination) disturbance (especially of seabirds). • Some shipping regulations related to environmental impacts are currently in place, and new regulations related to the IMO Polar Code and the IMO Ballast Water Management Convention will be important additions. These regulations do not, however, include guidelines for accidental (oil) spills, use of heavy fuel oil, or noise disturbance. • The BBDS region contains a number of areas of heightened ecological importance and significance. Though these areas are not necessarily ecologically vulnerable to environmental impacts from shipping (i.e., if there are no shipping-related activities or threats in the area), the foreseen changes in shipping may require longterm management and adaptation planning – that is, an adaptive ecosystem-based management (EBM) approach. • Very limited information is currently available on how ...